2011
DOI: 10.1097/cco.0b013e32834bb88e
|View full text |Cite
|
Sign up to set email alerts
|

Current status of allogeneic transplantation for aggressive non-Hodgkin lymphoma

Abstract: Purpose To provide a succinct update on the role of allogeneic stem cell transplantation in the management of patients with aggressive lymphomas. To clarify the indications for allogeneic transplantation vis-à-vis autologous transplant and to discuss the rational and potential benefits of reduced intensity conditioning(RIC), non-myeloablative (NMA) transplant, T-cell depletion and variations in GVHD prophylaxis. Recent findings Considerable effort has been spent in developing transplant regimens with reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 114 publications
0
17
0
Order By: Relevance
“…Nevertheless, because mortality associated with a second allo-HSCT for relapsed recipients is considered to be much higher, DLI therapy may represent a viable alternative to second allo-HSCT. Thus, DLI has been applied in the treatment of various hematological malignancies [6][7][8], such as leukemias [9,10], lymphoma [11][12][13], and myeloma [14,15]. In particular, patients who have relapsed after unrelated allo-HSCT because of lack of HLA-matched related sibling donors may also benefit from unrelated DLI (UDLI) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, because mortality associated with a second allo-HSCT for relapsed recipients is considered to be much higher, DLI therapy may represent a viable alternative to second allo-HSCT. Thus, DLI has been applied in the treatment of various hematological malignancies [6][7][8], such as leukemias [9,10], lymphoma [11][12][13], and myeloma [14,15]. In particular, patients who have relapsed after unrelated allo-HSCT because of lack of HLA-matched related sibling donors may also benefit from unrelated DLI (UDLI) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a considerable number of patients undergoing cyclophosphamide, doxorubicin, vincristine, and prednisone relapse thereafter or suffer from dose-related side effects and complications. Furthermore, stem cell transplantation, as a treatment of curing NHL, 2 is too expensive for patients, so curative treatment can be achieved in only a minority of NHL patients. Thus, novel therapeutic strategies are urgently needed to improve palliative treatment, prolong life expectancy, and improve quality of life in patients with lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…CBV is another common preparative regimen for auto-HSCT and was reported as a safe and an effective RIC for allo-HSCT in patients with NHL. [ 29 ] Many studies reported that the TRM in the setting of RIC was range from 20% to 44%. [ 25 ]…”
Section: Onditionning R Egimens For mentioning
confidence: 99%